STRUKTUR KOMUNITAS PLANKTON PADA WAKTU YANG BERBEDA DI TELAGA KUMPE BANYUMAS - Nur Haliza, Fitra Dwi; Rahayu, Diana Retna Utarini Suci; Sastranegara, Moh Husein (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Trade and tourism activities in Telaga Kumpe can increase the input of organic matter into the waters which results in increased fertility, decreased function and changes in water quality so that it has an impact on the community structure of plankton as one of the aquatic organisms. This study aims to determine the abundance, diversity, uniformity and dominance of plankton before sunrise (morning) and after sunrise (afternoon) as well as differences in the ratio of plankton abundance before sunrise and after sunrise (afternoon) in Kumpe Lake. . The research was carried out at three sampling points, namely at the inlet, in the middle of the lake and at the outlet. The main parameters measured included the number of individuals and plankton species, while the supporting parameters included physico-chemical factors in the waters, namely water temperature, light intensity, depth, pH and TDS levels. The results showed that the highest abundance of phytoplankton were Microcystis aeruginosa and Mougeotia viridis, while the highest abundance of zooplankton were Diaptomus siciloides and Cyclops vicinus. The diversity of plankton in the morning is included in the medium category, in the afternoon the low to moderate category. The uniformity of plankton in the morning and afternoon is in the low to high category. The plankton dominance index value in the morning indicates a dominant species, whereas during the afternoon it does not indicate a dominant species. The dominating species are Microcystis aeruginosa, Mougeotia viridis, Diaptomus siciloides and Cyclops vicinus. The results also show that the abundance of phytoplankton is higher during the day, and the abundance of zooplankton is higher in the morning